Filed and granted Indian Patents in dentistry from 2005-2009: A critical analysis and review - Mohammed Nadeem Ahmed Bijle; Shankargouda Patil (Wolters Kluwer Medknow Publications, 2013)
Background: Patent policies have proved to be extremely important for several countries to develop. India has achieved its global status since 2005; a critical analysis of the patents at IPO will help us to identify the potential, available for patents with Indian Dental Fraternity. Aim: The aim of this study is to critically analyze and review Indian Patents in the field of Dentistry from 2005-2009 for evaluation of status of Indian Patents in Dentistry. Materials and Methods: A total of 110 patents were scrutinized from 2005-2009 available by IPO on www.patentoffice.nic.in. Following which a preliminary data were collected from individual patents and recorded in a record sheet. Statistical Analysis: The data collected were analyzed using SPSS 16.0 software and were subjected to ANOVA test. Results: All patents scrutinized were applied for dental materials (100%). Company applicants (70%) were the maximum followed by the individual applicants (27.2%). A total of 87.3% of patents had enrolled for International Application. Priority country had maximum favor with USA (39.2%) followed by Europe (36.1%). Single inventors (44.5%) were the maximum followed by two inventors (22.7%). Europe (37.3%) had the maximum first inventor, followed by United States of America (30%) and India (10.9%). Individual inventors were maximum in Europe (38.8%) followed by USA (20.4%) and India (16.3%). Conclusion: Contribution from Indian Nationals as inventors for patents in the field of Dentistry is limited, thus reducing the pace of progress and development. Indian inventors in the field of Dentistry have to go a long way to compete with the fellow mates of developed countries like USA and Europe. Continuing Dental Education programs on Intellectual property rights should be conducted on regular basis especially for Dentist's involved in research.